Legal System for Endorsing Press Independency in Indonesia - Herlambang Perdana Wiratraman (Jember University Press, 2017)
Political transition of post Soeharto's authoritarian regime has been deeply influenced by a decentralised model of governance, which affected to more serious attacks to the journalism works. The extra-judicial killing, physical violence, criminalising against journalism, and other attacks through formal judicial process or other forms, included impunity system, have shown uneasy situation for journalist at field or members of the press to perform journalistic works. Violence against journalists at field in decentralised Indonesia has been more influenced by the role of political-economy contestation at the local level, rather than the influence of situation and policies at national level. The law enforcement to protect journalist at works seems easily deniable and disregarded due to law system itself that does not give significance effect. The court has been used to collapsing media, silencing opposition, retaliating, and terrorising journalism works. My research shows that the most targeted medias for ULAP (unjustifiable lawsuits against press) or criminalisation have been connected to its reliability, professionalism journalistic or high quality of news. On the other side, impunity has prevailed and become a dominant situation that is not merely caused by ‘external media’ factors, but also showed an ‘internal media’ factors. Avoiding the judiciary becomes phenomena that does not always relate to distrust over the judicial system, but more on a ‘forced situation’. In my presentation, I will show how this situation articulates a new configuration of political imperium which combines of free press and dominant ownership over media, plus illiberal democracy which legally allows and lets predatory system to be supreme class in the governance and other state institutions.